Synthesis, Biological Assessment and Molecular Modeling of Racemic QuinoPyranoTacrines for Alzheimer's Disease Therapy. Issue 2 (9th January 2018) - Chioua, Mourad; Serrano, Estefanía; Dgachi, Youssef; Martin, Hélène; Jun, Daniel; Janockova, Jana; Sepsova, Vendula; Soukup, Ondrej; Moraleda, Ignacio; Chabchoub, Fakher; Ismaili, Lhassane; Iriepa, Isabel; et al.
Abstract: In this report we describe the synthesis, biological evaluation and molecular modeling of new tacrine analogues such as QuinoPyranTacrines (QPTs), designed by juxtaposition of 1, 4‐naphthoquinone and tacrine. From these results we have identified QPT16 as a permeable, selective human acetylcholinesterase inhibitor [IC50 = 1.1 ± 0.15 μM], 3.5‐fold less‐hepatotoxic than tacrine at 1000 μM concentration, and consequently, a potential new hit‐compound for further investigation targeted to find a new agent for AD therapy. Abstract : The synthesis of (QPT16) in two steps, from 2‐hydroxynaphthalene‐1, 4‐dione, 4‐methoxybenzaldehyde, and malononitrile, followed by Friedländer‐type reation with cyclohexanone, has been described. QPT16 is a permeable, selective hAChE [IC50= 1.1 ± 0.15 mM], whose binding at hAChE has been investigated by docking analysis, 3.5‐fold less‐hepatotoxic than tacrine at 1000 M concentration, and consequently, a potential new hit‐compound for further investigation targeted to find a new agent for AD therapy.